Chapter Gender and Information and Communication Technologies interest: results from PISA 2018 - Zenga, Mariangela (Proceedings e report, 2021)
ICT engagement has become an important key driver regarding the competence for the adults, but even more for young people. As it was pointed out in 2015, ICT interest (a component of ICT engagement) is defined as "content-specific motivational disposition" and describes "individuals' long-term preference for dealing with topics, tasks, or activities related to ICT" (Goldhammer et al., 2017). Using data from 2018 Programme for International Student assessment (PISA), this work will show the gender difference in ICT interest for 15-years old students of 23 OECD countries. Moreover a three-level multilevel model will explain the effects of the characteristics of the student, of the school in which the student learns and of the country in which the student livis on the ICT interest.